The Impact of Long-Distance Running Exercise on Body Composition and Psychological Stress - Sukiri; Puti Hassanah; Harry Syahputra Nasution; Apta Mylsidayu (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2026)
This study aimed to examine the effects of structured long-distance running training monitored by wearable fitness trackers on body weight, body mass index (BMI), and perceived stress levels among overweight young adults. A quasi-experimental design with a pretest–posttest control group was employed involving 20 participants aged 20–25 years who were classified as overweight or mildly obese. Participants were divided into an experimental group (n = 10) and a control group (n = 10) with homogeneous baseline characteristics. The experimental group participated in a structured long-distance running program for 4–9 weeks, three times per week, at moderate intensity (60–70% HRmax), while the control group received only general health education. Body weight, BMI, and perceived stress (measured using the Perceived Stress Scale/PSS) were assessed before and after the intervention. The results showed significant reductions in body weight and BMI in the experimental group (p < 0.05), while no significant changes were found in the control group. Perceived stress scores also decreased significantly in the experimental group (p < 0.05). Pearson correlation and linear regression analyses revealed that training duration and frequency were significantly associated with improvements in BMI and stress levels. These findings indicate that structured long-distance running monitored with wearable technology is an effective non-pharmacological intervention for improving physical and psychological health among overweight young adults, particularly those exposed to sedentary lifestyles and elevated stress levels